IMPROVEMENT OF PREGNANT WOMEN'S PERCEPTION ON STUNTING PREVENTION THROUGH ISLAMIC-BASED PRENATAL CLASSES - Riani, Eka Oktarina; Devi Elvin, Said; Warnidar, Eka (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
One of the causes of stunting is the nutritional deficiency of pregnant women. To prevent stunting, pregnant women must be educated about nutrition through prenatal classes. The purpose of this research is to determine the effectiveness of Islamic-based prenatal classes in improving pregnant women's perceptions of stunting prevention. This research is a quasi-experimental study on pregnant women in the Meuraxa District of Banda Aceh. Power analysis is used to determine the sample size, resulting in 64 pregnant women in the intervention group and 64 pregnant women in the control group. The intervention consists of an Islamic-based prenatal class conducted in five sessions, each lasting sixty minutes. The data collection instrument to understand pregnant women's perceptions of stunting prevention was developed by the researcher based on the Health Belief Model (HBM) theory. Data collection was conducted twice, namely before the intervention (pre-test) and after the intervention. (post test). Data analysis used descriptive statistics, namely frequency distribution and non-parametric statistics, namely the Wilcoxon Signed Rank Test and the Mann Whitney U Test to assess the difference in mean scores between the intervention group and the control group. The research results indicated that there are differences in perceptions of pregnant women between the intervention group and the control group regarding the prevention of stunting in children, namely perceptions of vulnerability (P-value = 0.048), perceptions of severity (P-value = 0.015), perceptions of benefits (P-value = 0.048), and perceptions of barriers (P-value = 0.002). Based on the results, the Islamic-based prenatal class program for pregnant women has proven effective in enhancing the perception of pregnant women in preventing stunting in their unborn children as early as possible.